Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
PsycEXTRA Dataset 2004
DOI: 10.1037/e300802005-002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Mental Health Status of Youth in Juvenile Justice Settings

Abstract: Access OJJDP publications online at www.ojp.usdoj.gov/ojjdp with inadequate psychometrics, the failure to consider comorbidity (i.e., co-occurring conditions), problems with identifying sample characteristics, and a lack of information regarding when the assessments were conducted. They note that previous studies often did not define the timeframe for symptoms. However, distinguishing between lifetime and current symptoms is important not only for determining the prevalence of disorders but also in planning fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 22 publications
2
71
0
Order By: Relevance
“…For example, Teplin et al (2002) found no significant differences in the proportion of males (51%) compared to females (47%) in meeting criteria for a substance use disorder. Similarly, Wasserman et al (2004) found no significant differences between males (26%) and females (22%) in their sample of probation-involved youth. Conversely, Timmons-Mitchell et al (1997) found that a higher proportion of males (88%) had a substance use disorder than did females (56%) in their sample of incarcerated youth.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…For example, Teplin et al (2002) found no significant differences in the proportion of males (51%) compared to females (47%) in meeting criteria for a substance use disorder. Similarly, Wasserman et al (2004) found no significant differences between males (26%) and females (22%) in their sample of probation-involved youth. Conversely, Timmons-Mitchell et al (1997) found that a higher proportion of males (88%) had a substance use disorder than did females (56%) in their sample of incarcerated youth.…”
Section: Introductionmentioning
confidence: 85%
“…Substance use and mental health disorders are widespread among youth involved in the juvenile justice system, affecting between 40 and 70% of this population (Shufelt and Cocozza 2006;Teplin et al 2006;Timmons-Mitchell et al 1997;Wasserman et al 2004). Prevalence estimates suggest that one of out every five youth involved in the juvenile justice system has serious mental health problems C. L. Welch-Brewer .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asking juveniles in detention facilities about prior mental health issues and medication use is important because frequently used screening instruments (e.g., MAYSI-2) do not access this information. Wasserman, Ko, and McReynolds (2004) suggested best practices for clinical assessment in juvenile justice facilities which included use of multiple methods of mental health assessment along with information from multiple informants to obtain a thorough understanding of the detainee. For this reason, input from parents/caregivers, current or former teachers, and any other significant individual who has dealt with the individual is important.…”
Section: Screeningmentioning
confidence: 99%
“…During this time, studies examining screening and identification, assessment, and treatment outcomes have offered valuable information to those in the field. As previously discussed, the prevalence level for a diagnosable mental health disorder among all youth in the JJS is estimated to be as high as sixty-five to seventy percent (Shufelt & Cocozza, 2006;Teplin, Abram, McClelland, Dulcan, & Mericle, 2002;Wasserman & McReynolds, 2004). Furthermore, youth in the JJS experience mental health disorders at a rate more than three times higher than youth in the general population (Mental Health and Juvenile Justice Collaboration for Change, 2014).…”
Section: Chapter Two: Literature Reviewmentioning
confidence: 80%